Phrases constructed with turkish organ names in the hamdullah hamdî's yusuf u züleyhâ - Züleyha (Uluslararası Türk Lehçe Araştırmaları Dergisi)
Masnavi is a form of verse in which short forms of aruz are used and each couplet is rhymed among itself. Masnavis are important in that they convey the messages the poet wants to say to the society in a detailed and comfortable way. Yusuf u Züleyha Masnavi, one of the oldest religious masnavis, which is about the love of Prophet Yusuf and Zuleyha, has an important place both religiously and literaryly in terms of the messages it contains. In the study, the idioms formed with Turkish organ names in the last 4235 couplets of the Yusuf u Züleyha masnavi written by the Hamdullah Hamdî, one of the 15th century poets, were discussed. Examining the simile motifs in the idioms formed with the names of organs and elucidating the hidden bond between the literal meaning and the figurative meaning has an important place for linguistics research. Many studies have been carried out on organ names from past to present. Based on these studies, among the idioms formed with the names of organs, the most numerous idioms formed with the names of head, tongue, hand, heart, eye and facial organs are numerically more numerous. In this study, the idioms established with the names of these basic organs of the body and other organs will be identified and classified according to the organs, and the idiom will be shown in bold form at the beginning, and on the right side, the transfer of the idiom to today's Turkish, followed by the example couplet it is in, the transfer of the example couplet to today's Turkish and in parentheses. The number of couplets of the couplet will be specified. Afterwards, these idioms will be given in alphabetical order and the total number of idioms formed by organ names in the work will be determined. Thus, it will be stated whether these idioms identified in the 15th century period work continue to be used in today's Turkish.